In vitro evaluation of hemostatic properties of the sap of Jatropha multifida L. (Euphorbiaceae) - DOUGNON, T. VICTORIEN; KLOTOE, J.R.; SEGBO, JULIEN A. GAÉTAN; LOKO, CHRISTIAN FRÉDÉRIC SIMPLICE (My University, 2012)
Jatropha multifida L. is a plant widely used in traditional medicine in Benin including some voodoo ritual practices, to stop bleeding. In this study, we investigated in vitro haemostatic properties of the sap of J. multifida L. Morphological observations and determination of some biochemical and hematological parameters were performed on whole blood, plasma and serum before and after addition of sap. Results obtained showed sap contains tannins, flavonoids, saponins, leucoanthocyanes, mucilage and reducing compounds. When added to plasma or serum, proteins precipitated sap and led to (<1 s) their constitution network very quickly. On whole blood, the addition of sap led to an instantiated coagulation. Microscopic observations have revealed that cells have reached (<1 s) the protein network formed which led to the formation of a cell aggregate. Apart from fibrinogen, which was significantly reduced, other coagulation factors are not modified by sap. The sap has a proven hemostatic property and its mechanism of action is different from the cascade reaction of coagulation.
Keywords: Coagulation; protein network; tannins; cell aggregate.